2016
DOI: 10.1016/j.alcohol.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different stressors on voluntary ethanol intake in ethanol-dependent and nondependent C57BL/6J mice

Abstract: Several animal models have evaluated the effect of stress on voluntary ethanol intake with mixed results. The experiments reported here examined the effects of different stressors on voluntary ethanol consumption in dependent and nondependent adult male C57BL/6J mice. In Experiment 1, restraint, forced swim, and social defeat stress procedures all tended to reduce ethanol intake in nondependent mice regardless of whether the stress experience occurred 1 h or 4 h prior to ethanol access. The reduction in ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 57 publications
12
66
0
Order By: Relevance
“…Results from Experiment 1 are consistent with previous work our laboratory that demonstrated daily FSS selectively augmented ethanol consumption in CIE-exposed mice, but not control mice (Lopez et al, 2016). In the current study, FSS facilitated the emergence of escalated drinking in CIE-exposed mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from Experiment 1 are consistent with previous work our laboratory that demonstrated daily FSS selectively augmented ethanol consumption in CIE-exposed mice, but not control mice (Lopez et al, 2016). In the current study, FSS facilitated the emergence of escalated drinking in CIE-exposed mice.…”
Section: Discussionsupporting
confidence: 89%
“…In a recent study from our laboratory, we also observed differential effects of stress on ethanol consumption in dependent compared to nondependent animals. More specifically, using our dependence and relapse drinking model involving chronic intermittent ethanol (CIE) exposure, daily forced swim stress exposure prior to drinking sessions further elevated home cage limited access ethanol consumption in dependent (CIE-exposed) mice but did not alter intake in nondependent mice (Lopez et al, 2016). …”
mentioning
confidence: 99%
“…For example, rats exhibit increased stress responsiveness following withdrawal from chronic alcohol exposure, as measured by several experimental procedures that provoke behavioral measures of stress/anxiety, such as reduced social interaction in a novel environment, reduced exploration in threatening circumstances (e.g., open, brightly illuminated spaces), and greater electroshock-induced suppression of ongoing behavior (Breese et al, 2005; Gehlert et al, 2007; Sommer et al, 2008). In a series of studies involving a mouse model of alcohol dependence and relapse drinking, repeated brief exposure to forced swim stress prior to alcohol drinking sessions significantly increased drinking in alcohol dependent mice, but did not alter intake in nondependent mice (Lopez et al, 2016). Interesting, this stress procedure did not further increase drinking in two other drinking models that typically engender high levels of alcohol intake – the drinking-in-the-dark (DID) model and the intermittent access (‘every-other-day’) model (Anderson et al, 2016a).…”
Section: Link Between Chronic Alcohol Stress Response and Motivamentioning
confidence: 99%
“…There are many reasons for this void in the literature, not the least of which is the complexity of combining the models used to study each of these disorders. At the most basic level, it has been notoriously difficult to produce models in which stress reliably increases alcohol drinking for a sustained period of time (Boyce‐Rustay et al , ; Croft et al ; Funk et al ; Lopez et al ; McKenzie‐Quirk & Miczek ; Miczek et al ; Sillaber et al ; van Erp & Miczek ). The field has been more successful in producing animal models that mimic the ability of stressors to elicit relapse to seeking of alcohol and other drugs, in which animals are trained to self‐administer alcohol or drugs of abuse, this responding is extinguished and stress is used to reinstate responding for an alcohol or drug reinforcer that is not actually available to the animal; these models have been reviewed in detail elsewhere (see Mantsch et al ).…”
Section: Modeling Comorbid Ptsd and Aud In Animalsmentioning
confidence: 99%